Impact of T161, Y318 and S363 alanine mutations on regulation of the human delta-opioid receptor (hDOPr) induced by peptidic and alkaloid agonists. (15th November 2020) - Camacho, Elise; Marie, Nicolas; Dupas, Quentin; Martel, Caroline; Nowoczyn, Marie; Elie, Nicolas; Rochais, Christophe; Töth, Geza; Allouche, Stéphane
Abstract: Previously, we showed a differential regulation of the human delta-opioid receptor (hDOPr) by etorphine and [D-Pen 2, D-Pen 5 ] enkephalin (DPDPE). To understand the molecular basis of such differences, we introduced 3 alanine mutations at the residues T161. Y318 and S363. Both wild type (WT) and hDOPr mutants were expressed in HEK cells containing endogenous arrestins or CFP-tagged arrestin 3, then desensitization, internalization, recycling and phosphorylation were studied. In a context of endogenous arrestin expression, a major difference in DOPr desensitization was observed between agonists that was modified with the T161A mutation upon etorphine and with the S363A substitution upon DPDPE exposure. While both agonists induced a major receptor internalization, T161A and S363A impaired DOPr sequestration only for etorphine. However, similar level of S363 phosphorylation was measured between agonists. When CFP-tagged arrestin 3 was over-expressed, a similar profile of desensitization was measured for both agonists. In this context, all the 3 alanine mutations decreased etorphine-induced receptor desensitization. Using FRET, we showed similar interactions between WT hDOPr and arrestin 3 under DPDPE and etorphine stimulation which were delayed by both the Y318A and the S363A substitutions for etorphine. Finally, hDOPr recycling was qualitatively evaluated by microscopy and showed neither arrestin 3/hDOPr colocalization nor major impact of alanine mutations except for the S363A which impaired internalization and recycling for etorphine. The T161, Y318 and S363 residues of hDOPr could underlie the differential regulation promoted by DPDPE and etorphine. Graphical abstract: Image 1 Highlights: T161 and S363 residues are involved in the differential hDOPr desensitization. Arrestin 3 over-expression allows similar desensitization between DPDPE and etorphine. T161 and S363 are involved in hDOPr internalization for etorphine but not DPDPE. S363 phosphorylation level is not correlated to hDOPr desensitization. Y318A and S363A mutations delay hDOPr and arrestin 3 interactions only upon etorphine.